2014
DOI: 10.1155/2014/920467
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for Prevention of Preeclampsia in Lupus Pregnancy

Abstract: Preeclampsia, the onset of hypertension and proteinuria during pregnancy, is a common medical disorder with high maternal and fetal mortality and morbidity. The underlying pathology remains poorly understood and includes inflammation, endothelial dysfunction, and an unbalanced thromboxane A2/prostacyclin ratio. For women with systemic lupus erythematosus (SLE), particularly those with preexisting renal disease or with active lupus, the risk of developing preeclampsia is up to 14% higher than it is among health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…This is, amongst others, derived from studies finding a beneficial effect of aspirin in other populations at high risk for HD or intra-uterine growth (10). Furthermore, treatment with LMWH in addition to treatment with aspirin was advised for women with either primary or secondary APS in review and overview articles (7,9,17,18). In women with SLE and aPL, authors of two retrospective studies suggested that LMWH treatment during pregnancy might be beneficial to reduce maternal and perinatal pregnancy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is, amongst others, derived from studies finding a beneficial effect of aspirin in other populations at high risk for HD or intra-uterine growth (10). Furthermore, treatment with LMWH in addition to treatment with aspirin was advised for women with either primary or secondary APS in review and overview articles (7,9,17,18). In women with SLE and aPL, authors of two retrospective studies suggested that LMWH treatment during pregnancy might be beneficial to reduce maternal and perinatal pregnancy …”
Section: Discussionmentioning
confidence: 99%
“…Due to limited sideeffects and proven beneficial effects in other high-risk populations, the recommendation to use aspirin in the prevention of pregnancy complications was extended to women with SLE and primary APS (7,10).…”
Section: <0001mentioning
confidence: 99%
See 1 more Smart Citation
“…A later follow-up meta-analysis demonstrated that LDA initiated at or before 16 weeks reduces the risk of severe, but not mild, preeclampsia (124). Although lupus and/or aPL-positive patients are not included in these studies, these patients are at increased the risk of preeclampsia (125). Thus, independent of aPL, several groups recommend LDA for all lupus patients, even without a history of pregnancy morbidity (117,118,(126)(127)(128); however, there are no clinical trials supporting this recommendation.…”
Section: First Pregnancy Morbidity Preventionmentioning
confidence: 99%
“…This oligonephropathy increases risk for systemic and glomerular hypertension in adult life. [97][98] Additionally, the hypoxic and pro-inflammatory environment of the maternofetal unit results in epigenetic programming which impinges on the child's cardiometabolic and neuropsychiatric health. [ The anti-platelet drug aspirin is recommended for pre-eclampsia prevention.…”
mentioning
confidence: 99%